2010
DOI: 10.1038/nature09627
|View full text |Cite
|
Sign up to set email alerts
|

COT drives resistance to RAF inhibition through MAP kinase pathway reactivation

Abstract: Oncogenic mutations in the serine/threonine kinase B-RAF are found in 50–70% of malignant melanomas1. Pre-clinical studies have demonstrated that the B-RAFV600E mutation predicts a dependency on the mitogen activated protein kinase (MAPK) signaling cascade in melanoma1–5—an observation that has been validated by the success of RAF and MEK inhibitors in clinical trials6–8. However, clinical responses to targeted anticancer therapeutics are frequently confounded by de novo or acquired resistance9–11. Identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,085
2
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,330 publications
(1,145 citation statements)
references
References 29 publications
30
1,085
2
13
Order By: Relevance
“…5,24), with recent clinical studies reporting that highly specific BRAF inhibitors are effective in the treatment of metastatic melanoma (25)(26)(27). However, initial promise has been hampered by the development of resistance (28)(29)(30), which is characterized by the reactivation of ERK1/2 (31)(32)(33) and has been attributed to various mechanisms including activating NRAS mutations (29), CRAF overexpression (34), compensatory upregulation of MAP2K kinase COT (28), activating MEK1 mutations (35), and amplification of mutant BRAF (36).…”
Section: Introductionmentioning
confidence: 99%
“…5,24), with recent clinical studies reporting that highly specific BRAF inhibitors are effective in the treatment of metastatic melanoma (25)(26)(27). However, initial promise has been hampered by the development of resistance (28)(29)(30), which is characterized by the reactivation of ERK1/2 (31)(32)(33) and has been attributed to various mechanisms including activating NRAS mutations (29), CRAF overexpression (34), compensatory upregulation of MAP2K kinase COT (28), activating MEK1 mutations (35), and amplification of mutant BRAF (36).…”
Section: Introductionmentioning
confidence: 99%
“…Levi Garraway, an oncologist at the Dana-Farber Cancer Institute in Boston, Massachusetts, and his colleagues have now found that excessive production of a cancer-promoting protein called COT can shield cultured cells from PLX4032. High levels of COT were also found in two of three PLX4032-resistant tumours taken from patients who had received the drug 3 .…”
Section: By H E I D I L E D F O R Dmentioning
confidence: 90%
“…For V5-A-Raf, A-Raf from pDONR223-ARAF (Addgene Plasmid 23725) 86 was fused N-terminal with a V5-tag of pcDNA6.2/V5-DEST using Gatway technology.…”
Section: Methodsmentioning
confidence: 99%